PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS IV UPT SDN 03 AIRPURA - Julianti, Cici; Fitria, Yanti; Zuryanty; Media, Afriza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research uses a Classroom Action Research (PTK) approach with mixed methods that combines qualitative and quantitative elements. Each cycle consists of planning, implementation, observation and reflection stages. This research involved teachers and 15 class IV students 6 boys and 9 girls at UPT SDN 03 Airpura in the 2026/2027 academic year. Data collection includes assessment of teaching modules, observation of teacher and student activities, as well as assessment of student attitudes, knowledge and skills. Data is collected through observation, tests and documentation. The research results indicate that student learning outcomes in Social Studies (IPS) improved from Cycle I to Cycle II. In the planning stage, the teaching module assessment score rose from 84.72% (Good) in Cycle I to 96.53% (Very Good) in Cycle II. In the implementation stage, teacher-related aspects improved from 82.14% (Good) in Cycle I to 95.83% (Very Good) in Cycle II. Student learning outcomes also showed improvement: the score for the attitude aspect rose from an average of 79.33 (Good) to 92.67 (Very Good); the score for the knowledge aspect increased from an average of 74.67 to 89.33; and the score for the skills aspect rose from an average of 76.00 to 91.33. Thus, it can be concluded that the implementation of the Problem-Based Learning (PBL) model can improve the Social Studies learning outcomes of fourth-grade students at UPT SDN 03 Airpura.